Perceptual-cognitive skills of basketball referees: On-the-court visual search behavior - Ruiz, A. J.; Albaladejo-García, C.; Reina, R.; Moreno, F. J. (Perceptual and Motor Skills, 2024)
Perceptual-cognitive skills are crucial in successfully managing information and decision-making in sports, particularly in high-pressure environments. We examined 16 basketball referees` on-the-court visual search behavior by comparing referees of different experience levels (experienced, n = 8; and novice, n = 8) and different court positions. Participants` visual search behavior was analyzed during 20 live gameplay situations using eye-tracking technology. Dependent variables were the number of eye fixations, mean fixation time, and total fixation time on selected areas of interest; and independent variables were the referees` experience and visual angles (lead and trail referee positions). Experienced referees exhibited significantly lower total fixation time than novice referees (p = .009). Referees in the trail position showed more fixations of shorter duration and a greater focus on the basket than those in the lead position. Our findings suggest that the visual search behavior of basketball referees varies with their court position and experience. These data provide valuable insights into referees` complex visual search patterns in the real-game context, and they highlight the importance of considering viewing angle and experience in future research.